Intraventricular Tumor: An Analysis of 18 Cases (Bangladesh Journal of Neuroscience, 2015)
Objective: To describe the transcallosal and transcortical approach to deal with intraventricular tumors.Methods: Details of the transcallosal and transcortical approach to intraventricular tumors of the lateral and third ventricles were presented.Results: Intraventricular tumors are ideal indications for microscopic neurosurgery. They often cause cerebrospinal fluid (CSF) pathway obstruction, resulting in ventricular dilatation. The general principle of removal of intraventricular tumors was interruption of the blood supply to the tumor and subsequent tumor debulking. In general, a piecemeal resection was performed; however, in some tumors such as meningioma, it was possible to detach the lesion from the surrounding brain tissue and remove it in toto. When the tumor found in the anterior part of the third ventricle, the craniotomy was done at the coronal suture. When the tumor was located in the posterior part, the entry craniotomy was selected more anteriorly in order to pass the foramen of Monro in a straight line.Conclusion: Intraventricular tumors and related CSF pathway obstructions can be safely and effectively treated with micro neurosurgical techniques, either by transcallosal or transcortical approach. The aim should be the total extraction of the tumor with minimum damage and the chosen operative corridor should optimize tumor access and the protection of vulnerable neurovascular structures. Lateral ventricle tumors can be removed via transcortical approach when having hydrocephalus which provides a wider and more direct approach to the tumor than the transcallosal one. It allows the surgeon to achieve good functional outcome and maximum excision of the tumor. Transcallosal is an excellent midline exposure with preserving the callosomerginal and pericallosal arteriesto the midline tumor of lateral and 3rd ventricles.Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 94-101